To compare the efficacy of alternate day versus everyday dosing of atorvastatin in hyperlipidemic rabbits - Mulkalwar, Sarita; Golande, Pravin (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Muscle pain is often seen with statin therapy. Statins have also been associated with increase in liver transaminases as they lead to hepatic injury. The half - life of atorvastatin is increased due to its active metabolites which suggest the possibility for its alternate day use over everyday use. This would mean reduction in side effects such as hepatotoxicity and myopathy and solving the problem of statin underutilization in patients of lower socio economic class. Methods: Institutional Animal Ethics Committee (IAEC) approval was taken before the start of study. Hyperlipidemia was induced in New Zealand White rabbits by oral administration of high fat diet for 3 weeks. After 3 weeks all the laboratory tests were done to see if animals had developed hyperlipidemia. This day was considered as day 0 for further study. Hyperlipidemic rabbits were divided into two groups, first group receiving atorvastatin orally (5mg/kg) daily for duration of 6 weeks while the other group receiving atorvastatin orally (5mg/kg) at alternate days for same duration. All the laboratory tests were done at week 3 and week 6. Both the treatment groups were compared pairwise and also with day 0 to check for efficacy and safety. Results: At the end of 6 weeks every day and alternate day dosing of atorvastatin, showed a statistical decrease in total cholesterol, triglycerides and LDL-C with respect to day 0. Pairwise comparison did not show any statistical difference in between the two treatment groups. Statistical increase in HDL-C was seen only with everyday dosing of atorvastatin as compared to day 0. Pairwise comparison showed statistical difference in between two treatment groups. At the end of 6 weeks, there was no statistical difference in SGOT, SGPT and CK levels when compared to day 0. Conclusions: Alternate day dosing of atorvastatin was as efficacious and safe as everyday dosing of atorvastatin in hyperlipidemic New Zealand White rabbits, thus being a cost effective alternative.